2016
DOI: 10.1017/s1355617716000746
|View full text |Cite
|
Sign up to set email alerts
|

CVLT-II Forced Choice Recognition Trial as an Embedded Validity Indicator: A Systematic Review of the Evidence

Abstract: In the absence of serious neurocognitive disorder, FCR ≤14 is highly specific, but only moderately sensitive to invalid responding. Passing FCR does not rule out a non-credible presentation, but failing FCR rules it in with high accuracy. The heterogeneity in sample characteristics and reference PVTs, as well as the quality of the criterion measure across studies, is a major limitation of this review and the basic methodology of PVT research in general. (JINS, 2016, 22, 851-858).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(27 citation statements)
references
References 47 publications
(43 reference statements)
3
24
0
Order By: Relevance
“…Veterans were included in the performance valid group (PVT-Pass) if they performed above cutoffs on all PVT indices. These measures have been widely used to detect poor performance validity in Veterans with TBI history (Flaherty, Spencer, Drag, Pangilinan, & Bieliauskas, 2015;Jak et al, 2015;Lippa, 2018, Whitney, Davis, Shepard, Bertram, & Adams, 2009Young et al, 2016) and have shown adequate sensitivity, specificity (false positive rates <10%), and positive predictive power (Denning, 2012(Denning, , 2014Fazio, Denning, & Denney, 2017;Haber & Fichtenberg, 2006;Kulas, Axelrod, & Rinaldi, 2014;Schwartz et al, 2016;Spencer et al, 2013;Tombaugh, 1997;Young, Sawyer, Roper, & Baughman, 2012). Furthermore, it has been recommended that failure of even one PVT should warrant consideration of performance invalidity, particularly for tests with adequate positive predictive power used in populations with relatively high base rates including individuals with remote history of mTBI (Denning, 2019;Inman & Berry, 2002;Iverson & Franzen, 1996;Lippa, 2018;Proto et al, 2014;Vickery et al, 2004).…”
Section: Performance Validity Testsmentioning
confidence: 99%
“…Veterans were included in the performance valid group (PVT-Pass) if they performed above cutoffs on all PVT indices. These measures have been widely used to detect poor performance validity in Veterans with TBI history (Flaherty, Spencer, Drag, Pangilinan, & Bieliauskas, 2015;Jak et al, 2015;Lippa, 2018, Whitney, Davis, Shepard, Bertram, & Adams, 2009Young et al, 2016) and have shown adequate sensitivity, specificity (false positive rates <10%), and positive predictive power (Denning, 2012(Denning, , 2014Fazio, Denning, & Denney, 2017;Haber & Fichtenberg, 2006;Kulas, Axelrod, & Rinaldi, 2014;Schwartz et al, 2016;Spencer et al, 2013;Tombaugh, 1997;Young, Sawyer, Roper, & Baughman, 2012). Furthermore, it has been recommended that failure of even one PVT should warrant consideration of performance invalidity, particularly for tests with adequate positive predictive power used in populations with relatively high base rates including individuals with remote history of mTBI (Denning, 2019;Inman & Berry, 2002;Iverson & Franzen, 1996;Lippa, 2018;Proto et al, 2014;Vickery et al, 2004).…”
Section: Performance Validity Testsmentioning
confidence: 99%
“…However, current guidelines for cognitive evaluation in MS do not include a recommendation for assessment of performance validity (Kalb et al, 2018), and recommended cognitive batteries for MS patients (e.g., MACFIMS, BICAMS) do not include standalone PVTs (Benedict et al, 2002;Langdon et al, 2012). Both of these batteries include an embedded PVT, the CVLT-II forced choice recognition trial (FCR; Delis et al, 2000); however, its utility in MS has not been examined, and a recent systematic review showed that CVLT-II FCR has shown poor sensitivity to nonvalid responding in the absence of severe cognitive impairment (Schwartz et al, 2016). Notably, our clinical battery also included the CVLT-II FCR, but was not included in this study because it was only administered to 54 of the patients who were administered the VSVT.…”
mentioning
confidence: 99%
“…As a result, their validity on the short form at least should continue to be interpreted with some caution. Second, the study did not collect information on participants' history of attention deficit hyperactivity disorder, language disorders, or learning disabilities, all of which have shown associations with CVLT performance (e.g., Schwartz et al, 2016). To characterize how CVLT-II SF performance differs among different psychiatric disorders, future work is needed to examine these associations in diverse samples.…”
Section: Discussionmentioning
confidence: 99%